Estimation of the Radon Risk Under Different European Climates and Soil Textures - Gil-Oncina, Sara; Valdes-Abellan, Javier; Pla, Concepcion; Benavente, David (Frontiers in Public Health, 2022)
Radon is a radioactive gas produced from the natural radioactive decay of uranium and is found in almost all rocks and soils. In confined places (e.g., dwellings, workplaces, caves, and underground mines), radon may accumulate and become a substantial health risk since it is considered the second most important cause of lung cancer in many developed countries. Radon risk assessment commonly considers either field or estimate values of the radon concentration and the gas permeability of soils. However, radon risk assessment from single measurement surveys to radon potential largescale mapping is strongly sensitive to the soil texture variability and climate changes, and particularly, to the soil water content dynamic and its effect on soil gas permeability. In this paper, the gas permeability of soils, and thus, the estimation of radon risk, is studied considering the effect of three different climates following the Köppen classification and four soil textures on soil water content dynamics. This investigation considers the CLIGEN weather simulator to elaborate 100-year length climatic series; Rosseta 3 pedotransfer function to calculate soil hydraulics parameters, and the HYDRUS-1D software to model the dynamics of water content in the soil. Results reveal that climate strongly affects gas permeability of soils and they must be considered as an additional factor during the evaluation of radon exposure risk. The impact of climate and texture defines the soil water content dynamic. Coarse soils show smaller gas permeability variations and then radon risk, in this case, is less affected by the climate type. However, in clay soils, the effect of climate and the differences in soil water content derive in gas permeability variations between 100 and 1,000 times through an annual cycle. As a result, it may cross the boundary between two radon risk categories. Results deeply confirm that both climate and texture should be compulsory considered when calculating the radon exposure risk and in the definition of new strategies for the elaboration of more reliable geogenic radon potential largescale maps.